Antimicrobial activity and substantivity of Uncaria tomentosa in infected root canal dentin - Daniel Rodrigo HERRERA; Jorge Enrique DURAND-RAMIREZ; Amanda FALCÃO; Emmanuel João Leal Nogueira da SILVA; Elizabete Brasil dos SANTOS; Brenda Paula Figueiredo de Almeida GOMES (Brazilian Oral Research, 2016)
Abstract The aim of this study was to analyze the antimicrobial activity and substantivity of Uncaria tomentosa Willd DC (cat’s claw, CC) in root dentin contaminated with Enterococcus faecalis. Forty-eight human premolars were contaminated with E. faecalis (ATCC 29212) and randomly divided into four groups according to the irrigant used during chemomechanical preparation (CMP): CC group: 2% CC gel; CHX group: 2% chlorhexidine digluconate gel (CHX); NaOCl group: 5.25% sodium hypochlorite (NaOCl); and SS group: sterile saline (SS). Microbiological samples were collected before (S1) and after (S2) CMP and after 7 days (S3). Colony-forming units (CFU/mL) at the different sampling times and comparisons among the groups were statistically analyzed by Wilcoxon and Kruskal-Wallis tests (p < 0.05). Significant bacterial reduction was achieved in all groups after CMP (p < 0.05). Results show no significant difference between S3 and S2 (p > 0.05) in the CC and CHX groups. Bacterial load was higher in S3 than in S2 samples (p < 0.05) in the NaOCl and SS groups. Our results suggest antibacterial effect of 2% CC gel against E. faecalis in infected dentin, in addition to antibacterial substantivity of 2% CC and 2% CHX up to 7 days.